Crop yield, water use efficiency and economic assessment of purple broccoli (Brassica oleracea) across varied water and nitrogen management practices - KIRUTHIGA, B; SINGH, MAN; KHANNA, MANOJ; SINGH, SHRAWAN; PARIHAR, C M; BANDYOPADHYAY, K K; KUMAR, S NARESH; RAJPUT, JITENDRA; N, KISHOR (The Indian Journal of Agricultural Sciences, 2023)
Inefficient management of irrigation and fertilizers emerges as the primary hurdle constraining the crop performance, profitability of broccoli (Brassica oleracea L. var. italica) production, resource wastage and environmental harm. To address this issue, a field experiment was conducted during winter (rabi) seasons of 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi. The research focused on investigating the effect of irrigation techniques and nitrogen management on broccoli yield, water use efficiency (WUE) and economic feasibility. The two main irrigation methods of drip irrigation and furrow irrigation as main factor, 2 irrigation regimes of full irrigation (100% ETC) and limited irrigation (75% ETC) as sub-factor, 3 nitrogen doses (N) of 125, 100 and 75% recommended dose of N as sub-sub factor were given and replicated thrice. The study aimed to analyse the yield, water use efficiency and assessment of economics under diverse irrigation water and N-management approaches. Under drip irrigation the mean yield and water-use efficiency shown substantial increase by 12 and 52% in comparison with furrow irrigated purple broccoli grown under the same condition. The highest benefit to cost (B:C) ratio of 3.81 and 4.79 was obtained in the treatment DRI1N1 during 2020–21 and 2021–22, respectively. Undoubtedly, the significance of adequate irrigation regime (100% ETC) and optimal N dose (125% RDN) became apparent, as they played significant roles in enhancing crop performance and ensuring the attainment of maximum broccoli yield, WUE and economics in Trans-Gangetic Plains region.